Expression of a dominant T-cell receptor can reduce toxicity and enhance tumor protection of allogeneic T-cell therapy - Angelika Holler; Mathias Zech; Sara Ghorashian; Rebecca Pike; Alastair Hotblack; Pedro Veliça; Shao-An Xue; Ronjon Chakraverty; Emma C. Morris; Hans J. Stauss (Haematologica, 2016)
Due to the lack of specificity for tumor antigens, allogeneic T-cell therapy is associated with graft-versus-host disease. Enhancing the anti-tumor specificity while reducing the graft-versus-host disease risk of allogeneic T cells has remained a research focus. In this study, we demonstrate that the introduction of ‘dominant’ T-cell receptors into primary murine T cells can suppress the expression of endogenous T-cell receptors in a large proportion of the gene-modified T cells. Adoptive transfer of allogeneic T cells expressing a ‘dominant’ T-cell receptor significantly reduced the graft-versus-host toxicity in recipient mice. Using two bone marrow transplant models, enhanced anti-tumor activity was observed in the presence of reduced graft-versus-host disease. However, although transfer of T-cell receptor gene-modified allogeneic T cells resulted in the elimination of antigen-positive tumor cells and improved the survival of treated mice, it was associated with accumulation of T cells expressing endogenous T-cell receptors and the development of delayed graft-versus-host disease. The in vivo deletion of the engineered T cells, mediated by endogenous mouse mammary tumor virus MTV8 and MTV9, abolished graft-versus-host disease while retaining significant anti-tumor activity of adoptively transferred T cells. Together, this study shows that the in vitro selection of allogeneic T cells expressing high levels of a ‘dominant’ T-cell receptor can lower acute graft-versus-host disease and enhance anti-tumor activity of adoptive cell therapy, while the in vivo outgrowth of T cells expressing endogenous T-cell receptors remains a risk factor for the delayed onset of graft-versus-host disease.